MANAJEMEN PENDIDIKAN ISLAM BERBASIS TAHFIDZ DI PONDOK PESANTREN TAHFIZH QUR`AN AHMAD DAHLAN PONOROGO - Panusunan Rambe; Syarifan Nurjan; Sigit Dwi Laksana (Universitas Muhammadiyah Ponorogo, 2019)
Management in an educational institution is one of the most important considerations for parents in choosing educational institutions for their sons. The management of tahfizh-based Islamic education in PPTQ Ahmad Dahlan Ponorogo is all educational activities that exist in PPTQ Ahmad Dahlan Ponorogo. The purpose of this research is to find out the management of Islamic education in PPTQ Ahmad Dahlan Ponorogo. The purpose of this study was to find out the management in PPTQ Ahmad Dahlan Ponorogo because Islamic Education is not only for santri but also for the people around Ponorogo to learn about Islam and the Qur'an. In addition to this, every santri is obliged to memorize the Qur'an in addition to formal education. The method used in this study is a qualitative descriptive method and the data collection is done by interview, observation, and documentation. Data analysis techniques used in this study include data reduction, data presentation and conclusions. The conclusion of the results of this study is that the management of Islamic education in Ahmad Dahlan Ponorogo's PPTQ has been carried out based on the principle of the obligation of every santri. The management of Islamic education carried out is not only aimed at santri but also for the people around Ponorogo.